2017
DOI: 10.17221/403/2016-pse
|View full text |Cite
|
Sign up to set email alerts
|

Soil respiration and net ecosystem production under different tillage practices in semi-arid Northwest China

Abstract: In semi-arid areas, increasing CO<sub>2</sub> emissions are threatening agricultural sustainability. It is unclear whether different tillage practices without residue returned could help alleviate these issues while increasing crop productivity. This study aimed to quantify soil respiration under conventional tillage (CT); rotary tillage (RT); subsoiling (SS) and no-till (NT), all without residue returned in the Western Loess Plateau. The results showed that SS and NT significantly decreased soil r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…For example, Jiang et al [61] reported higher respiration rate in the soil depth of 0-20 cm under combination of ridge with no-tillage than under conventional tillage. On the contrary, in the study by Lamptey et al [62], higher CO 2 release was noted in soil under conventional tillage, while subsoiling and no-till decreased carbon emissions by 20% on average. Other authors [63] have not demonstrated significant differences in SBR between the CT and NT (no-till) systems.…”
Section: Effects On Soil Basal Respirationmentioning
confidence: 72%
See 1 more Smart Citation
“…For example, Jiang et al [61] reported higher respiration rate in the soil depth of 0-20 cm under combination of ridge with no-tillage than under conventional tillage. On the contrary, in the study by Lamptey et al [62], higher CO 2 release was noted in soil under conventional tillage, while subsoiling and no-till decreased carbon emissions by 20% on average. Other authors [63] have not demonstrated significant differences in SBR between the CT and NT (no-till) systems.…”
Section: Effects On Soil Basal Respirationmentioning
confidence: 72%
“…Similar findings published by Hazarika et al [64] showed that microbial biomass contents in soil under no-till and/or reduced tillage systems were markedly higher compared with conventionally tilled soil, which also supports our results. in the study by Lamptey et al [62], higher CO2 release was noted in soil under conventional tillage, while subsoiling and no-till decreased carbon emissions by 20% on average. Other authors [63] have not demonstrated significant differences in SBR between the CT and NT (no-till) systems.…”
Section: Effects On Microbial Biomass Carbon and Nitrogenmentioning
confidence: 84%
“…For the annual crops, spring wheat, and millet were sown by a locally designed traditional seeder (6 rows in 1.2 m width), with seeding rate of 187.5 and 15 kg ha −1 , respectively. Maize was sown with alternate wide (0.7 m) and narrow (0.4 m) ridges at a density of 52,500 plants ha −1 , as described by Lamptey et al [25] Potato was sown using a plant spacing of 0.30 m to achieve a density of 52,500 plants ha −1 . All the annual crops were planted with conventional tillage, where the field was annually rotary ploughed twice: once in fall after crop harvest and the other in spring when sown, while crop residue was removed manually from the plots after harvest.…”
Section: Experimental Design and Treatment Descriptionmentioning
confidence: 99%
“…For example, Zhang et al (2009) proved that different tillage systems are significantly different in terms of soil CO 2 emission and have various potential to greenhouse effect reduction. As far as it was mentioned that no-till is not always the best option, Lamptey et al (2017) established that subsoil tillage provides the best effect on carbon emissions cutting compared to conventional moldboard and zero tillage. Apart from that, subsoiling also benefits rational water use and provides sustainable yielding of crops.…”
Section: Introductionmentioning
confidence: 99%